Formulasi Lip Gloss Ekstrak Daun Karamunting (Rhodomyrtus tomentosa) dengan Variasi Konsentrasi Biji Kesumba Keling (Bixa orellana L.) dan Cera Alba - Chandra, M. Andi; Afra, Fairuz Yaumil; Rahmiati, Nur; Forestryana, Dyera; Nabila, Amaliya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This experimental study aims to determine the physical characteristics and stability of lip gloss from karamunting leaf extract with variations in the concentration of 0.5-2.5% kesumba keling seeds and 1-9% cera alba. Based on the organoleptic test, the preparation has an orange to reddish orange color, a semi-solid preparation form, a distinctive odor, and is homogeneous. The pH range value is 5.48-5.97, the spread area of ​​Formula I-III is 5.0-5.6 cm, the spread area of ​​Formula IV and V is 4.0-5.3 cm does not meet the spreadability requirements, the lip gloss has good spreadability, and the preference assessment is mostly preferred in Formula II. The stability test showed no changes in organoleptic and homogeneity and there were significant changes in pH and spreadability during the cycling test. There was an increase in pH and spreadability but still within the required range. The conclusion of this study, the lip gloss preparation from karamunting leaf extract Formula I-III produced met the requirements while Formula IV and V did not meet the spreadability requirements.